2016
DOI: 10.1016/j.jinorgbio.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional chiral copper (II) complexes with novel nano-structures and superior antitumor activity

Abstract: Three novel copper(II) compounds of formulas {[Cu(Phen)(Ala)]·NO3·H2O}n (1), {[Cu(Phen)(Ala)]·NO3}n (2) and [Cu(Ala)2]n (3) have been synthesized and determined by X-ray diffraction. 1 and 2 are shown in one dimensional long-chain chiral structures, and 3 is a two dimensional checkerboard-type structure. Both 1 and 2 displayed a higher anticancer activity than 3 against various cancer cells, even higher than the similar mononuclear complexes and clinical anticancer drug 5-fluorouracil. The noncancerous cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These 98 data sets being published in 80 different articles show the lack of systematic exploration of the crystal structures and structure-property relationship of such copper( ii ) ternary coordination compounds. Only in two research articles different solvates of these ternary coordination compounds were investigated – monohydrate and unhydrated alaninato complexes [ 16 ] and six serinato solvates involving water and/or methanol [ 5 ]. Both described alaninato compounds are coordination polymers, where carboxylic group acts as bridge between two copper(II) atoms.…”
Section: Introductionmentioning
confidence: 99%
“…These 98 data sets being published in 80 different articles show the lack of systematic exploration of the crystal structures and structure-property relationship of such copper( ii ) ternary coordination compounds. Only in two research articles different solvates of these ternary coordination compounds were investigated – monohydrate and unhydrated alaninato complexes [ 16 ] and six serinato solvates involving water and/or methanol [ 5 ]. Both described alaninato compounds are coordination polymers, where carboxylic group acts as bridge between two copper(II) atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and design of chiral metal complexes have attracted a considerable amount of attention because they can bind to DNA, and changes their photophysical properties [1]. In previous work, DNA binding and cleavage studies of chiral copper complexes have been broadly investigated [14][15][16][17][18][19]; however, study on Schiff bases copper complexes with chiral amino-alcohols have rarely been reported [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%